The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fnut.2022.1047932
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant properties of water-soluble polysaccharides prepared by co-culture fermentation of straw and shrimp shell

Abstract: Herein, we present a method for producing water-soluble polysaccharides (WSPs) by co-culture fermentation of straw and shrimp shells. The chitin-degrading strain was isolated and genotypically identified as the non-pathogen Photobacterium sp. LYM-1 in this study. Photobacterium sp. LYM-1 and Aureobasidium pullulans 2012 could coexist without antagonism. WSPs concentrations were higher in co-culture fermentations of Photobacterium sp. LYM-1 and A. pullulans 2012 (PsL/AP-WSPs) compared to monocultures (PsL-WSPs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 67 publications
(78 reference statements)
0
5
0
Order By: Relevance
“…Appropriate temperature is important for the growth, metabolism and reproduction of microorganisms (Lyu et al ., 2022). Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Appropriate temperature is important for the growth, metabolism and reproduction of microorganisms (Lyu et al ., 2022). Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The sugar content in purified FOs was determined by the phenol–sulfuric acid method with Glc as the standard (de Borba et al ., 2022). The content of protein was determined by the Bradford method using bovine serum albumin as the standard (Lyu et al ., 2022). The content of total flavonoids was determined by the previous method using rutin as the standard (Martin‐Diana et al ., 2021).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have confirmed that fruits and vegetables can produce exopolysaccharides after fermentation. ( Lyu et al, 2022 ) used sugarcane juice as raw material and fermented sugarcane juice with ganoderma lucidum at 28 °C and found that after fermentation, the content of extracellular polysaccharide and protein were significantly increased, and free amino acids were significantly enriched. The antioxidant activity test showed that exopolysaccharide has the ability to scavenge hydroxyl radicals, superoxide anion radical and DPPH (Diphenyl-1-picrylhydrazyl) radical.…”
Section: Bioactive Ingredients Of Fermented Fruit and Vegetable Juicementioning
confidence: 99%
“…LYM-1 and Aureobasidium pullulans 2012 were co-cultured and cultured separately; subsequently, the water-soluble polysaccharides (WSPs) produced in fermentations of each strain and the co-culture were extracted and used for OH• scavenging assays, separately. With each of the measured concentrations, the WSPs from co-culture exhibited a stronger ability to scavenge OH• than the other two WSPs factions [65].…”
Section: Oh• Radical Scavenging Activitymentioning
confidence: 99%